DISP-04. PATIENTS WITH PROGRESSION OF SPINE METASTASES WHO PRESENT TO CLINIC HAVE BETTER OUTCOMES COMPARED TO THOSE WHO PRESENT TO THE EMERGENCY DEPARTMENT. (14th November 2022) - Strong, Michael; Kathawate, Varun; Goethe, Peyton; Tudrick, Lila; Linzey, Joseph; Ward, Ayobami; Zaki, Mark; Joshi, Rushikesh; Jackson, William; Szerlip, Nicholas
Abstract: As cancer therapies have improved, survival has increased. Spine metastases are becoming more common in the course of oncologic disease. Complications arising from these metastases have a significant impact on patient quality of life and the optimal method to follow these patients and avoid deficits has not yet been adequately studied. The purpose of this study was to identify characteristics of a subgroup of oncologic patients with metastatic spinal disease. Retrospective analysis of oncological patients ( > 18 years) who underwent stereotactic body radiation therapy (SBRT) to the spine at the University of Michigan, from 2010 to 2020 was performed. A total of 395 radiographic isocenters in 298 patients were identified. Of these, 112 isocenters in 83 patients and 283 isocenters in 215 patients were treated after presenting to the ED or clinic, respectively. As expected, patients presenting to the ED had more deficits compared to the clinic (severe pain (30% vs 6%); difficulty ambulating (48% vs 8%); weakness (25% vs 6%); or myelopathy (11% vs 1%). Social economic factors including marital status, insurance type, and having a primary care physician were similar between groups. Of the 112 ED isocenters, 58 required surgery plus SBRT (52%); while 54 required SBRT only (48%). Additionally, of the 283 clinic isocenters, 53 required surgery plus SBRT (19%); while 230 only required SBRT (81%). The overall survival was higher for clinic compared to ED (12.6mos vs 8.5mos), respectively. Interestingly, even when surgical intervention was taken into consideration, those presenting to the ED still had poorer outcomes compared to clinic (6.7mos vs 13.3mos), respectively. Metastatic spinal disease patients who present to the ED have poorer survival than those who present to the clinic. A better understanding of the factors that drive this phenomenon is warranted in order to improve the management and outcomes of this population.